GDP vs genuine progress quantification of economic performance in South Korea and Malaysia - Hashim, Mastura; Mohammad Sifat, Imtiaz; Mohamad, Azhar (Oviedo University Press, 2018)
Malaysia and South Korea, successful graduates of Asian Financial Crisis, employed different paths to recovery via Capital Control and IMF bail-out respectively. This paper tracks recovery trajectories of the two nations via orthodox and emergent growth indicators: GDP and GPI. We report unemployment, open-trade, fixed capital accumulation, and prior crisis to be influential determinants of both metrics, while credit and foreign exchange rate lack significance.